Performa Kontroler MPC Berbasis Fungsi Laguerre dan Kontroler PID Untuk Kendali Konverter Buck-Boost - Adelhard Beni Rehiara; Yanty Rumengan (Retii, 2020)
The buck-boost converter is a device to change the amount of DC electricity. This device is very non-linear, so a better controller is needed to improve its performance. In this research, a Laguerre function based MPC has been made to control the converter. A simulation to determine the performance of the MPC on the buck-boost converter is done by comparing it with the existing PID controller. The simulation setting is done by providing an input voltage of 55V with loads of 25W, 60W and 100W within a setpoint of 100V. The simulation results show that the MPC has a high response speed in the order of milliseconds even though there is still an overshoot of 12.4% when compared to the PID controller which does not have overshoot but has a slower response with a little steady state errors and some spikes along the simulation.